Fasting plasma glucose is an independent predictor for severity of H1N1 pneumonia - Sun Xiwen; Wang Jiajun; Qiu Bo; Li Qiang; Chen Hong; Wang Wei; Xiang Ying; Zhang Jinchao (BMC Infectious Diseases, 2011)
Abstract Background The pandemic influenza A (H1N1) virus emerged during 2009 and has spread worldwide. This virus can cause injuries to the lungs, liver, and heart. However, data regarding whether this influenza virus can affect pancreatic islets are limited. We investigated the effects of influenza A (H1N1) pneumonia on fasting plasma glucose (FPG) and islet function, and evaluated possible correlations between biochemical test results and the severity of H1N1 pneumonia. Methods We performed a retrospective analysis of patients either diagnosed with or suspected of having H1N1 pneumonia who were admitted to our hospital in 2009. Possible associations between FPG levels and H1N1 virus infection were assessed by logistic regression. Correlation and regression analyses were used to assess relationships between FPG and biochemical test results. Associations between admission days and significant data were assessed by single factor linear regression. To evaluate effects of H1N1 on pancreatic β-cell function, results of a resistance index (homa-IR), insulin function index (homa-β), and insulin sensitivity index (IAI) were compared between a H1N1 group and a non-H1N1 group by t-tests. Results FPG was significantly positively associated with H1N1 virus infection (OR = 1.377, 95%CI: 1.062-1.786; p = 0.016). FPG was significantly correlated with AST (r = 0.215; p = 0.039), LDH (r = 0.400; p = 0.000), BUN (r = 0.28; p = 0.005), and arterial Oxygen Saturation (SaO2; r = -0.416; p = 0.000) in the H1N1 group. H1N1 patients who were hypoxemic (SaO2<93%) had higher FPG levels than those who were not hypoxic (9.82 ± 4.14 vs. 6.64 ± 1.78; p < 0.05). FPG was negatively correlated with SaO2 in the H1N1 group with hypoxia (SaO2<93; r = -0.497; p = 0.041). SaO2 levels in patients with high FPG levels (≥7 mmol/L) were significantly lower than those of H1N1 patients with low FPG levels (<5.6 mmol/L). There were no significant differences in homa-IR, homa-β, or IAI between the H1N1 and non-H1N1 groups after adjusting for age, sex, and BMI. Conclusions FPG on admission could be an independent predictor for the severity of H1N1 pneumonia. Elevated FPG induced by H1N1 pneumonia is not a result of direct damage to pancreatic β-cells, but arises from various factors' combinations caused by H1N1 virus infection.